Employee engagement and the blind spots of managerial accounting: A narrative review - Haryanto, Haryanto; Setiawan, Amelia; Astuti, Tutut Dewi; Putra, Rino Dwi (Edelweiss Applied Science and Technology, 2026)
Managerial accounting has long prioritized calculability, standardization, and financial control while often overlooking relational and affective dimensions of labor that are central to organizational value. This review addresses the absence of employee engagement in managerial accounting and positions it as a critical object of inquiry. Using a narrative review methodology, the study synthesizes literature published between 2020 and 2025, drawing on Human Capital Theory, Agency Theory, the Resource-Based View, and Stakeholder Theory. The approach emphasizes conceptual integration, reflexive interpretation, and genealogical tracing across accounting, human resource management, and organizational studies. The results indicate that engagement is consistently marginalized across four domains of managerial accounting: performance measurement, cost attribution, budgeting, and disclosure. Engagement is often outsourced to HR functions or treated as a discretionary expense, despite growing evidence that it contributes to innovation, retention, and resilience. The significance of this study lies in reframing engagement as both an economic and ethical dimension of accounting. The review advances a triadic conceptual framework of sensing, translating, and signaling to demonstrate how engagement can be recognized as a substantive accounting object. While interpretive in scope, the study offers important implications for policy, practice, and future cross-disciplinary research.